Formulate the quadratic function that contains the points (-1,4), (0,2) and (2,4).

f(x) = x2 + x + 2
f(x) = x2 + x - 2
f(x) = x2 - x + 2
f(x) = x2 - x - 2

Respuesta :

f(x) = x2 - x + 2

f(-1)=(-1)²-(-1)+2=4   contain the point (-1,4)

f(0) = 0²-0+2 = 2   contain  the point (0,2)

f(2) = 2²-2+2 =4   contain the point (2,4)

Answer:

[tex]f(x)=x^2-x+2[/tex]

Step-by-step explanation:

Quadratic equation form : [tex]y=ax^2+bx+c[/tex]   --1

We are given points :(-1,4), (0,2) and (2,4).

Substitute the point (0,2) in the quadratic equation.

[tex]2=a(0)^2+b(0)+c[/tex]

[tex]2=c[/tex]

Thus the value of c is 2

Substitute the value of c in 1

Thus equation becomes: [tex]y=ax^2+bx+2[/tex]   --2

Now substitute the point (-1,4) in 2

[tex]4=a(-1)^2+b(-1)+2[/tex]

[tex]4=a-b+2[/tex]

[tex]a-b=2[/tex]    ---3

Now substitute point (2,4) in 2

[tex]4=a(2)^2+b(2)+2[/tex]

[tex]4=4a+2b+2[/tex]

[tex]2=2a+b+1[/tex]

[tex]2a+b=1[/tex]   --4

Now solve 3 and 4 to find the value of a and b

Substitute the value of a from 3 in 4

[tex]2(2+b)+b=1[/tex]

[tex]4+2b+b=1[/tex]

[tex]4+3b=1[/tex]

[tex]3b=-3[/tex]

[tex]b=-1[/tex]

Substitute the value of b in 3

[tex]a-(-1)=2[/tex]

[tex]a+1=2[/tex]

[tex]a=2-1[/tex]

[tex]a=1[/tex]

Thus a = 1, b =-1 and c = 2

Substitute the values in 1

[tex]y=x^2-x+2[/tex]

Thus the quadratic function that contains the points (-1,4), (0,2) and (2,4) is   [tex]f(x)=y=x^2-x+2[/tex]

Hence Option 3 is correct.